Hubungan Aktivitas Fisik Dengan Tingkat Depresi Pada Warga Binaan Pemasyarakatan (WBP) Dilapas Perempuan Kelas II Pondok Bambu Jakarta Timur Dan Tinjauan Nya Menurut Pandangan Islam - Aura Nasywa Lokananta; Trisiswati, Maya (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Correctional inmates (WBP) are faced with conditions in correctional institutions (prisons) that have limited space for movement and psychological pressure, which can affect their mental health, including increasing the risk of depression. This study aims to analyze the relationship between physical activity and depression levels in Correctional Inmates (WBP) at the Class II Pondok Bambu Women's Prison, East Jakarta, as an effort to provide a deeper understanding of the role of physical activity in reducing depression levels. This study uses a quantitative design with a cross-sectional study approach where independent and dependent variables are collected in the same period and the impact is measured according to the conditions at the time of the study. Data collection was carried out by distributing questionnaires with guided interviews to respondents who met the criteria in 78 samples selected using purposive sampling techniques. (1) Measurement results using IPAQ indicate that inmates' physical activity is dominated by the low category, followed by the moderate and high categories. (2) Inmates' responses indicate that the majority of inmates fall into the mild, moderate, and severe depression categories. (3) Bivariate analysis shows a significant relationship between physical activity levels and depression levels in inmates (p < 0.001). (4) The research findings regarding the relationship between physical activity and depression align with Islamic views, which emphasize the importance of maintaining physical health to support spiritual health.